2N Parameter Solutions to the Burgers’ Equation - solutions, We construct real parameter solutions to the Burgers' equation in terms of determinant of order; we call these; ., order solutions. We deduce general expressions of these solutions in terms of exponentials; study the patterns of these solutions in functions of the parameters for until (Journal of Applied Nonlinear Dynamics, 2026)
We construct 2N real parameter solutions to the Burgers’ equation in terms of determinant of order N and we call these solutions, N order solutions. We deduce general expressions of these solutions in terms of exponentials and study the patterns of these solutions in functions of the parameters for N=1 until N=4.